(Technical Design and Testing of Soy Milk Extractor in Tofu Production) - Rizal Alamsyah Alamsyah; Atih Suryati Herman Suryati Herman; Sri Wuri Handono Wuri Handono (Balai Besar Industri Agro, 1987)
The extraction of soy milk in tofu production in Indonesia was done by traditional pressing in which the ground soy mixture was wrapped in cotton cloth and pressed using a piece of stone. In this way some amount of soy milk was still left in the presscake. The study is aimed at designing two types of extractor-centrifugal type and press type-in order to increase the extraction efficiency. It was found that the liquid content of presscake obtained from this equipment is less as compared to the traditional method. The capacity of centrifugal is 270 1/hr. Its efficency of the centrifugal is 84.04% and those of press type is 69.50%. The optimal rotation of sieve of the centrifugal machine is about 700 rpm using induction motor of 1.5 HP.